Tandem triggering of wormlike micelles using CO2 and redox. Issue 86 (3rd October 2016) - Zhang, Yongmin; Yang, Chengcheng; Guo, Shuang; Chen, Hui; Liu, Xuefeng
Abstract : Wormlike micelles reversibly and tandemly respond to biocompatible CO2 and redox, which in turn leads to a change in their rheological properties. Abstract : Wormlike micelles constructed from a selenium-containing surfactant and a commercial diamine through a simple combination strategy can reversibly undergo a tandem reaction in response to CO2 and redox, exhibiting a transition between a gel-like fluid and a water-like fluid due to the evolution of aggregate structures from wormlike micelles to spherical micelles.